Analysis of pressure field generated by a collapsing bubble. (1st May 2016) - Li, S.; Han, R.; Zhang, A.M.; Wang, Q.X.
Abstract: This paper is concerned with the dynamic pressure induced by a collapsing bubble, based on the potential flow theory coupled with the boundary element method. The pressure is calculated using the Bernoulli equation, where the partial derivative of the potential in time is calculated using the auxiliary function method. The numerical results agree well with experimental results, in terms of bubble shape and pressure fields. There are two root causes of the bubble induced pressure and the dynamic pressure is decomposed into two parts correspondingly. The first part p g is associated with the imbalanced pressure between the bubble gas and the ambient flow, which measures the contribution of the high pressure gas to the dynamic pressure. The second part p m is caused by the bubble motion, which helps evaluate the contribution of the jet impact. The variation of p g has the same pattern with the gas pressure. p m at the wall center reaches its first peak soon after the jet impact, and then decreases due to the reduction of jet velocity. As the toroidal bubble migrates towards the wall, p m may rise again. We also investigate the influences of dimensionless parameters on the pressure field induced by a gas/cavitation bubble. Highlights: The dynamic pressure induced by a collapsing bubble is studied based on boundary element method. The toroidal bubble splitting phenomenon is simulated by using multiple vortex rings model. The numerical results agree well with experimental results, in terms of bubble shape and pressure fields. The bubble induced pressure is decomposed into two parts theoretically: the first one is caused by the bubble gas pressure and the second one is induced by the bubble motion. The pressure decomposition reveals some mechanisms of cavitation erosion or underwater explosion bubble damage. The influences of some dimensionless parameters on bubble induced pressure are investigated.